A Comparison of Relative Time to Peak and Tmax for Mismatch-Based Patient Selection - Wouters, Anke; Christensen, Søren; Straka, Matus; Mlynash, Michael; Liggins, John; Bammer, Roland; Thijs, Vincent; Lemmens, Robin; Albers, Gregory W.; Lansberg, Maarten G. (Frontiers in Neurology, 2017)
Background and Purpose: The PWI (perfusion weighted imaging) / DWI (diffusion weighted imaging) mismatch profile is used to select patients for endovascular treatment. A PWI map of Tmax is commonly used to identify tissue with critical hypoperfusion. A time to peak (TTP) map reflects similar hemodynamic properties with the added benefit that it does not require AIF selection and deconvolution. We aimed to determine if TTP could substitute Tmax for mismatch categorization. Methods: Imaging data of the DEFUSE 2 trial were reprocessed to generate relative TTP (rTTP) maps. We identified the rTTP threshold that yielded lesion volumes comparable to Tmax >6s and assessed the effect of reperfusion according to mismatch status, determined based on Tmax and rTTP volumes. Results: Among 102 included cases, the Tmax >6s lesion volumes corresponded most closely with rTTP >4.5s lesion volumes: median absolute difference 6.9 ml (IQR: 2.3-13.0). There was 94% agreement in mismatch classification between Tmax and rTTP-based criteria. When mismatch was assessed by Tmax criteria, the odds ratio (OR) for favorable clinical response associated with reperfusion was 7.4 (95% CI 2.3-24.1) in patients with mismatch vs. 0.4 (95% CI 0.1-2.6) in patients without mismatch. When mismatch was assessed with rTTP criteria these ORs were 7.2 (95% CI 2.3-22.2) and 0.3 (95% CI 0.1-2.2) respectively. Conclusions: rTTP yields lesion volumes that are comparable to Tmax and reliably identifies the PWI/DWI mismatch profile. Since rTTP is void of the problems associated with AIF selection, it is a suitable substitute for Tmax that could improve the robustness and reproducibility of mismatch classification in acute stroke.